An Indonesian Empirical Study of The Relationship between Firm’s Intellectual Capital, Financial Performance and Market Value - Silviani, Debby Andria; Noekent, Vitradesie (Universitas Negeri Semarang, 2020)
The purpose of this study is to explain the effect of Intellectual Capital on the company’s financial performance and market value. The population used in this study are all large trasing subsector companies listed on the Indonesia Stock Exchange during the 2009-2018 studi period. The sampling technique in this study uses a purposive sampling technique that uses criteria that have been determined by researches in order to obtain a sample of 13 companies. The testing tool used is Partial Least Square (PLS) version 2.0. The result of this study indicate that there is a positive and significant influence of intellectual capital on the company’s financial performance and intellectual capital also has a positive and significant on the company’s market value.The suggestion in this research is companie wish to consider the use of intellectual capital to improve financial performance and market value of the company.